PERILAKU MORAL KEHIDUPAN BERBANGSA DALAM PEMIKIRAN HAMKA - Sudin Sudin (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2014)
The moral values in life hold great importance from the point of personal, social and spiritual development. The quality of our lives is not determined by the happenstance of genetics or by the influence of environment; it is not measured in material possessions or in the trappings of youth; it is not dependent on personality or social acclaim. On the contrary, the intrinsic value of the lives we lead reflects the strength of a single trait: our personal character. Values are the motive power behind purposeful action. Moral values are meant for making the quest to find the higher  self an easier. This article explain those important matter as explained by Abdul Malik Karim Amrullah Al Hajj or was usually known as HAMKA (1908-1081) an expert ulama in religious field from Indonesia.